Racial Realism: A Review Essay on John Skrentny's After Civil Rights - Lang, Kevin (Journal of Economic Literature, 2015)
In his valuable contribution, After Civil Rights, John Skrentny shows that in many sectors of the labor market, race is used in ways that were unanticipated when the 1964 Civil Rights Act was enacted. With separate chapters on the professions and business, the public sector, media and entertainment, and the low-skill market, he demonstrates that the new racial realism is widespread, generally has some justification from social scientific research, and is usually inconsistent with judicial decisions. I review the racially realistic practices (racial matching, increasing diversity, racial signaling, and racial characteristics) and discuss their implications for labor economics and for policy. (JEL J15, J24, J71, J81, K31)